PENGARUH MASSASE TERHADAP INTENSITAS NYERI PUNGGUNG PADA IBU HAMIL - mardliyana, nova elok (Universitas Muhammadiyah Surabaya, 2020)
Objective: The discomfort that is often experienced by pregnant women in the second and third trimesters is back pain. Back massage with a gentle touch in the hip area can relieve lower back pain during pregnancy. The purpose of this research is to determine whether massage affects the intensity of back pain in pregnant women.Methods: This study used a quasi-experimental design with pre and post-test type one group design. The population of this study was all third-trimester mothers who experienced back pain at Public Health Center Tanah Kalikedinding Surabaya in May-August 2020; samples were taken by Accidental Sampling, so 32 respondents were obtained. This study used univariate and bivariate data analysis using Wilcoxon.Results: Back pain in third-trimester pregnant women before a back massage has an average of 4.42; after a back massage, the moderate pain is 3.18. There is an effect of back massage on back pain in third-trimester pregnant women. Statistical test results obtained t-test value and p-value 0.000 > 0.05.Conclusion: There is an effect of back massage on back pain in third-trimester pregnant women at Public Health Center Tanah Kalikedinding Surabaya. Pregnant women who experience back pain are expected to increase their knowledge about back massage so that it can be applied at home.